Development of a Science Literacy-Based E-module to Improve Science Learning Outcomes for Fourth Grade Students - Ila Nur Maulida; Novialita Angga Wiratama (Journal of Elementary Education, 2025)
This research focuses on the low learning outcomes of students in the IPAS subject about different energy forms. The study aims to assess the validity, practicality, and effectiveness of a science literacy-based e-module for fourth-grade students. It follows the Research and Development (R&D) method using the ADDIE model, which has five stages: Analyze, Design, Development, Implement, and Evaluation. The participants were 29 fourth-grade students from SDN Plaosan and class teacher. Data were collected through interviews, observations, questionnaires, and tests. The e-module met eligibility criteria with high validation scores: 86% for material, 84% for media, and 93. 3% for language. Teacher and student practicality scores were 88% and 94. 75%, respectively. The effectiveness score was 78%. In conclusion, the e-module is valid, practical, and effective for enhancing learning outcomes in fourth-grade classrooms.